Psychosocial hazards and work-life balance: the role of workplace conflict, rivalry, and harassment in Latvia - Diāna Inga Paegle; Svetlana Lakiša; Linda Matisāne; Monta Matisāne; Linda Paegle; Kristīne Mārtinsone; Daiga Kamerāde; Daiga Kamerāde; Valentīna Krūmiņa; Elīna Akmane; Amanda Ķule; Ivars Vanadziņš (Frontiers in Psychology)
BackgroundEven though the link between the psychosocial work environment and work-life balance (WLB) has been thoroughly researched, there is limited evidence evaluating the impact of workplace violence, sexual harassment, conflicts, and rivalry on WLB.MethodsA cross-sectional study was conducted among 2,471 respondents in Latvia from December 20, 2021, to July 14, 2022. WLB was measured through a survey question assessing the frequency of work-life imbalance, with responses categorized into dichotomous variables. The study evaluated the association between the selected workplace psychosocial hazards (conflicts, rivalry, psychological abuse, physical abuse, and sexual harassment), work characteristics, socio-demographic factors, and WLB by using binomial logistic regression.ResultsOur study reveals a significant lack of WLB among Latvian employees. A striking one-third of the respondents (30.9%, n = 762) reported experiencing this imbalance. The odds of WLB decrease with age, with the youngest age group having twice the odds compared to the oldest age group. Lower education levels and lower income groups also show significantly lower odds of WLB. Notably, those who have experienced selected workplace psychosocial hazards, such as sexual harassment or psychological abuse, have five- and three-times higher odds of work-life imbalance (aOR = 4.90 with 95% CI 2.06–11.67 and aOR = 3.47 with 95% CI 2.75–4.35, respectively). All types of conflicts at work significantly increase the odds of a lack of WLB. Our findings also indicate that WLB varies depending on various work characteristics, such as job position, work sector, company size, length of service, and remote or on-site work.ConclusionOur study highlights the importance of addressing WLB in the context of workplace conflicts, rivalry, violence, and harassment. It provides indirect evidence favoring leadership quality and manager training instead of employee training in diminishing psychosocial hazards. Practical implications include prioritizing leadership development programs focusing on conflict resolution and fostering a supportive organizational culture to improve employee WLB.